(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
According to WHO estimates, there were roughly 60,7 million cases of glaucoma in 2010 and will be 79,4 million cases by 2020. A cataract audit at the Sultanah Nur Zahirah Hospital, Kuala Terengganu, discovered that lens-related glaucoma affected 1.08% of cataract cases. This lens abnormality was a secondary glaucoma in which the crystalline lens had a role in the process causing elevated intraocular pressure (IOP). Secondary glaucoma is a glaucoma that occurs because of other underlying conditions. Glaucoma can be acute or chronic. Since acute glaucoma can result in lifelong blindness, it is a medical emergency that needs to be treated very away Understanding the warning signs and symptoms is crucial to preventing glaucoma-related lifelong blindness. A case of secondary glaucoma was presented in a 73 year old man who had ODS mature cataract and underwent OS phacoemulsification 1 day ago, now complaining of sudden redness and pain in the right eye accompanied by nausea and foggy vision. Vision OD 1/300. Ocular examination found narrow vision, hyperemic bulb conjunctive OD, conjunctive injection OD, corneal epithelial edema OD, shallow anterior chamber OD, curvy lens OD, mid-dilated pupil, shadow test negative, pupil reflex that cannot be evaluated, and IOL OS positive. A tonometry test was carried out and found IOP OD 30 mmHg, OS 13 mmHg. Fundoscope direct OD could not be assessed due to stiffness on the lens.